13C-DNA-SIP Distinguishes the Prokaryotic Community That Metabolizes Soybean Residues Produced Under Different CO2 Concentrations - Wang, Yanhong; Yu, Zhenhua; Li, Yansheng; Wang, Guanghua; Tang, Caixian; Liu, Xiaobing; Liu, Junjie; Xie, Zhihuang; Jin, Jian (Frontiers in Microbiology, 2019)
The amendment of crop residues produced under elevated CO2 (eCO2) may alter soil microbial community structure and their functions on residue decomposition and carbon (C) cycling in soil. The key to understanding this process is to elucidate the structure of prokaryotic communities that metabolize crop residues derived from eCO2. A soil incubation experiment was conducted to explore the response of soil microbial community to the amendment of 13C-labeled soybean residues produced under ambient CO2 (aCO2) and eCO2. The residues were applied to a Mollisol, followed by 13C-DNA stable isotope probing (SIP) and Illumina sequencing on soil prokaryotic community over time. The structure of residue-metabolizing community differed in response to the amendment of eCO2- and aCO2-derived residues after 28 days of incubation. In particular, genera Actinomadura, Nocardia, Nonomuraea and Shimazuella were the dominant members of the residue-metabolizing bacteria, which contributed to this difference. The abundances of genera Actinomadura, Nocardia and Shimazuella were 118–144%, 71–113% and 2–4 fold higher in the Mollisol amended with aCO2-derived than eCO2-derived residue. In contrast, the abundance of Nonomuraea was 87–90% greater in the eCO2-residue treatment. However, during the incubation period, there was no difference between the two residue treatments in the community structure as a whole without SIP. These results implied that a pioneering prokaryotic community metabolized the residue initially prior to the entire community. Those bacteria genera being inhibited with the amendment of the eCO2-derived residue, compared to aCO2-derived residue, were likely preferential to metabolize recalcitrant C, which might be associated with changes of chemical composition of the residue under eCO2.